2022
DOI: 10.1177/00104140211047403
|View full text |Cite
|
Sign up to set email alerts
|

How Soft Propaganda Persuades

Abstract: An influential body of scholarship argues that authoritarian regimes design “hard” propaganda that is intentionally heavy-handed in order to signal regime power. In this study, by contrast, we link the power of propaganda to the emotional power of “soft” propaganda such as television dramas and viral social media content. We conduct a series of experiments in which we expose over 6800 respondents in China to real propaganda videos drawn from television dramas, state-backed social media accounts, and state-run … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 62 publications
(91 reference statements)
1
23
0
Order By: Relevance
“…The second treatment, which criticized the United States, drew on three tweets from the Ministry of Foreign Affairs, and two from Zhao Lijian, who in addition to being deputy director 7 See Mattingly and Yao (2022) for an example of how similar messaging can stoke emotion and anti-foreign sentiment directed at another nation's people.…”
Section: Public Diplomacy Materialsmentioning
confidence: 99%
“…The second treatment, which criticized the United States, drew on three tweets from the Ministry of Foreign Affairs, and two from Zhao Lijian, who in addition to being deputy director 7 See Mattingly and Yao (2022) for an example of how similar messaging can stoke emotion and anti-foreign sentiment directed at another nation's people.…”
Section: Public Diplomacy Materialsmentioning
confidence: 99%
“…This led Huang (2015) to suggest that the Chinese state-run social media strategy involves hard and soft propaganda. Hard propaganda is biased information that frames the ruling party positively without mobilizing emotions, whereas soft propaganda involves emotional mobilization (Huang, 2015;Xia, 2020;Mattingly and Yao, 2022). Multiple studies have indicated that official Chinese propaganda outlets have achieved a delicate balance between positive and negative emotions to evoke emotional resonance and creative engagement (Kong, 2016;Fang and Repnikova, 2018;Gao and Wu, 2019), especially during the COVID-19 pandemic (Zhang, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They can use their media power to stir nationalist sentiments and shift the voters' attention away from the economy (Aytac ¸2021;Yilmaz et al 2021;Mattingly and Yao 2021). Yet, can authoritarian propaganda also be used to shape economic perceptions and performance evaluations, especially, during periods of economic decline?…”
Section: Introductionmentioning
confidence: 99%